Developing Scientific–Religious Character through the Integration of Islamic Values and Self-Regulated Learning in Science Education - Siti Mutiaraningsih Asshagab; Irwan Ledang; Muhtar Asshagab; Sri Milawati Asshagab; Enggal Mursalin (Universitas Tidar, 2025)
This study aims to examine the integration of Islamic values and self-regulation in science (IPA) learning and its role in developing students’ scientific–religious character. The study focuses on the “Matter and Energy” course in the second semester of the Science Education (Tadris IPA) Study Program in the 2024/2025 academic year. Science education is positioned not only as a process of mastering scientific concepts, but also as a means to internalize the values of Tawhid (the Oneness of God), cultivate a scientific mindset, and strengthen students’ responsibility as caliphs (stewards) in preserving the sustainability of Allah SWT’s creation. This research employs a qualitative descriptive approach with a purposive sampling technique involving eight students as research participants. Data were collected through classroom observations, in-depth interviews with lecturers and students, and analysis of students’ reflective learning documents compiled periodically. The data were analyzed thematically to reveal patterns of Islamic value integration, self-regulation practices, and their impact on student character development. The findings indicate that the integration of Islamic values is manifested through reflection on ayat kauniyah (signs of God in nature) relevant to energy concepts, the habituation of prayer in scientific activities, the implementation of responsible laboratory ethics, and the strengthening of ecological awareness as an expression of faith in action. Student self-regulation is reflected in their ability to set learning goals, manage learning strategies, monitor learning processes, and reflectively evaluate learning outcomes. The synergy between Islamic values and self-regulation fosters a scientific–religious character that is religious in intention, reflective in process, and independent in action, transforming science learning into a holistic and meaningful learning experience.